Finite deformation continuum model for mechanically induced phase transition in transition metal dichalcogenide monolayers. (September 2022) - Zhu, Wenqing; Mao, Sheng; Wei, Xiaoding
Highlights: We established a phase-field continuum mechanics model that accounts for both the finite deformation and mechanically induced phase transition of MoS2 and MoTe2 monolayers. Our approach can assess and reflect the competition between the phase transition and mechanical instability of MoS2 and MoTe2 . Our theory suggests that MoS2 monolayer under AFM indentation would fail prematurely before the phase transition completes, but MoTe2 monolayer remains stable to a large extent. Abstract: Tuning the electronic properties through phase engineering of two-dimensional transition metal dichalcogenides (TMDCs) is promising for their applications in electronic devices, energy conversion, and so on. Here, we establish a phase-field continuum mechanics model that accounts for both the finite deformation and mechanically induced phase transition of monolayer molybdenum disulfide (MoS2 ) and molybdenum ditelluride (MoTe2 ). Informed by first-principle calculations, our model can accurately describe not only the nonlinear mechanical behavior but also the phase transition criteria and processes driven by the mechanical energy. Applied to the nanoindentation tests on MoS2 drum specimens, the model reproduces well the force vs. depth curves and provides rich details on how the phase transition initiates and develops near the contact region. Further, based on the mechanical instability analysis, our study suggests that MoS2 monolayers under indentation tests would fail prematurely due to the mechanical instability in shear mode before the phase transition completes. In comparison, MoTe2 can finish the phase transition without worrying about mechanical instability, as observed in the indentation experiments. The model and methodology developed herein would serve as a powerful tool to guide the phase engineering of two-dimensional TMDCs.